THE PENGARUH BRAND IMAGE, BRAND TRUST DAN CELEBRITY ENDORSEMENT TERHADAP PURCHASE INTENTION PADA PELANGGAN SHAMPO CLEAR DI JAKARTA - Safitri, Tiya; Haryanti, Denny Septa (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This research aims to determine the effect of Brand Image, Brand Trust and Celebrity Endorsement on Purchase Intention of Clear shampoo customers in Jakarta. The population in this study was the customers of Clear shampoo who living in Jakarta. The samples were 141 respondents by purposive sampling method. The Assessment of each variable used five points of Likert Scale. Data processing used SPSS 25 software. The results of this study indicate that there is an influence effect of Brand Image, Brand Trust and Celebrity Endorsement on Purchase Intention of Clear shampoo customers in Jakarta.